Visual classification of braided and woven fiber bundles in X-ray computed tomography scanned carbon fiber reinforced polymer specimens. (November 2016) - Weissenböck, Johannes; Bhattacharya, Arindam; Plank, Bernhard; Heinzl, Christoph; Kastner, Johann
Abstract: In recent years, advanced composite materials such as carbon fiber reinforced polymers (CFRP) are used in many fields of application (e.g., automotive, aeronautic and leisure industry). These materials are characterized by their high stiffness and strength, while having low weight. Especially, woven carbon fiber reinforced materials have outstanding mechanical properties due to their fabric structure. To analyze and develop the fabrics, it is important to understand the course of the individual fiber bundles. Industrial 3D X-ray computed tomography (XCT) as a nondestructive testing method allows resolving these individual fiber bundles. In this paper, we show our findings when applying the method of Bhattacharya et al.[6] for extracting fiber bundles on two new types of CFRP specimens. One specimen contains triaxial braided plies in an RTM6 resin and another specimen woven bi-diagonal layers. Furthermore, we show the required steps to separate the individual bundles and the calculation of the individual fiber bundles characteristics which are essential for the posterior visual analysis and exploration. We further demonstrate the classification of the individual fiber bundles within the fabrics to support the domain experts in perceiving the weaving structure of XCT scanned specimens.